Dehydrogenation behavior and microstructure evolution of hydrogenated magnesium–nickel–yttrium melt-spun ribbons. Issue 67 (24th July 2015) - Song, Wenjie; Li, Jinshan; Zhang, Tiebang; Hou, Xiaojiang; Kou, Hongchao
<x xml:space="preserve">Abstract</x> High dehydrogenation kinetics are shown to be the result of a low activation energy combined with an amorphous and nanocrystalline structure.